Die großräumige Vergesellschaftung von Böden. Rechnergestützte Erfassung pedogenetischer Zusammenhänge, dargestellt am Beispiel der Bundesrepublik Deutschland - Kuhnt, Gerald (ERDKUNDE, 1989)
Due to the fact that the formation and development of soils are greatly influenced by a site- and time-related combination of fundamental factors like bed rock, climate, vegetation, topography etc. a detailed analysis of the distribution and association patterns of different soil types forms the basis for pedogenetic interpretations. For the soil cover of the Federal Republic of Germany it is shown that digital evaluations of soil maps, which include regionalization procedures, can be used for quantifying neighbourhood relationships between different kinds of soils. This results in a precise description of typical or less typical soil associations, sorted by the percentage of their occurrence. The amount of positive and negative auto-correlation, as displayed in matrix and graph form, yields better information on either the area and configuration of the various pedological units considered or their adjacent soils. Detailed interpretation leads to the conclusion that the methodology applied can be used for specifying interrelationships between soil distribution and pedogenesis within defined regions. The results obtained are considered the basis for a better understanding of soil formation and development under given conditions.